Kajian Hukum Dasar Penuntut Umum Menentukan Lamanya Hukuman Pada Penjatuhan Tuntutan Tindak Pidana Penganiayaan yang Mengakibatkan Cacat Permanen: Studi Putusan Pengadilan Negeri Nomor 371/Pid.B/2020/PN.Jkt.Utr - Kartika Chandra Kirana; Rugun Romaida Hutabarat (UNES Law Review, 2023)
The public prosecutor is indeed given freedom in determining charges and demands, including determining the time limit for a criminal sentence for a criminal offense being handled. Of course, the public prosecutor must remain guided by KUHP, KUHAP and Guideline No. 3/2019 concerning Prosecution, which can also refer to pre-existing prosecutions in similar cases. This is for the sake of creating legal certainty, benefit, and justice. However, unfortunately, in the case of the defendant Rahmat Kadir throwing acid on the victim, Novel Baswedan (an investigator with the Corruption Eradication Commission), The problem that wants to be studied is the basis for the public prosecutor to determine the time limit for punishment in the letter of prosecution for the crime of abuse that resulted in permanent disability in District Court Decision Number 371/Pid.B/2020/PN.Jkt.Utr. This research method is normative legal research with data in the form of secondary data supported by primary, secondary, and tertiary legal materials, where all data comes from literature studies. The approaches used are legislation (the status approach) and cases (the case approach), which are then analyzed using deductive methods. The results of this research show that the basis for the public prosecutor's considerations is very unclear and cannot be understood. By stating that the defendant was proven to have violated Article 353 paragraph (2) KUHP and demanded a sentence of only 1 (one) year in prison, The elements of inadvertence, cooperation, admitting mistakes, and requesting a request made by the defendant are also mitigating factors, while aggravating factors and other factors as stipulated in Guideline No. 3/2019 concerning Prosecution were actually ignored. This shows a bad portrait and an example of failure in implementing law enforcement by the public prosecutor to create the principles of legal certainty, benefit, and justice. On the other hand, in this case, the public prosecutor appears to be the defendant's representative legal advisor.